My iPhone - Miser, Brad (United Kingdom : Que, 2019)
"Step-by-step instructions with callouts to iPhone images that show you exactly what to do. Help when you run into iPhone problems or limitations. Tips and notes to help you get the most from your iPhone." -- Page 4 of cover.
Getting started with your iPhone -- Using your iPhone's core features -- Setting up and using an Apple ID, iCloud, and other online accounts -- Customizing how your iPhone works -- Customizing how your iPhone looks and sounds -- Managing contacts -- Communicating with the phone and FaceTime apps -- Sending, receiving, and managing email -- sending, receiving, and managing texts and iMessages -- Managing calendars -- Working with Siri -- Surfing the web -- Taking photos and video with your iPhone -- Viewing and editing photos and video with the photos app.
Keywords: iPhone (Smartphone).; Smartphones; Pocket computers; Digital music players